O computador no ensino da Matemática. Um estudo sobre concepções de professores - Azevedo, António Filipe Rodrigues de (1994)
This study aimed at researching mathematics teachers´ conceptions about mathematics and about the use of computers. We used a methology with a qualitative character, interviewing eight teachers of mathematics and following them in a teacher training program. Which involved meeting a and classes where computers were used. The results of this study suggest that computers are regarded as an instrument to integrate in the classroom, since they are motivating to the students, providing them with a more autonomous learning process, although some concerns about the role of the teacher still persist. These classes with computers resulted from the work of a team of teachers, who consider them to be harder than other classes. Geometry was referred to as the most adequate topic to use computers in the classroom, on the other hand, mathematics was considered differently by each teacher. It was also clear that the teacher´s instructional practices reflected their ideas, preoccupations and conceptions about the use of computers in the classroom.